2019
DOI: 10.3390/catal9121017
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement in Direct Methanol Fuel Cells by Using CaTiO3-δ Additive at the Cathode

Abstract: A non-stoichiometric calcium titanate CaTiO3-δ (CTO) was synthesized and used as oxygen reduction reaction co-catalyst (together with Pt/C) in direct methanol fuel cells (DMFCs). A membrane-electrode assembly (MEA), equipped with a composite cathode formulation (Pt/C:CTO1:1), was investigated in DMFC, using a 2 M methanol solution at the anode and oxygen at the cathode, and compared with an MEA equipped with a benchmark Pt/C cathode catalyst. It appears that the presence of the CTO additive promotes the oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…These results could be still attributed to the presence of oxygen defects on the CeO 2 structure which can create new oxygen adsorption pathway on the metal-oxide particles surface promoting the oxygen reduction reaction to proceed through the four-electron reduction pathway. [51] In accordance with the ECSA data reported in Table 1, we have recognized the composite Pt/C : CeO 2 1 : 1 sample as the most active catalyst among all those here investigated.…”
Section: Resultssupporting
confidence: 89%
“…These results could be still attributed to the presence of oxygen defects on the CeO 2 structure which can create new oxygen adsorption pathway on the metal-oxide particles surface promoting the oxygen reduction reaction to proceed through the four-electron reduction pathway. [51] In accordance with the ECSA data reported in Table 1, we have recognized the composite Pt/C : CeO 2 1 : 1 sample as the most active catalyst among all those here investigated.…”
Section: Resultssupporting
confidence: 89%
“…Yang et al [ 43 ] reported a study about an ultra-thin nickel oxide rich in oxygen vacancies, demonstrating that the presence of these oxygen defects can enhance the methanol oxidation reaction (MOR) performance. Furthermore, as reported in our previous work [ 20 ], it was demonstrated that CTO could improve the methanol oxidation if it is used as additive to Pt/C catalyst, confirming a promoting effect of the perovskite for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of iridium produced an enhancement of the electrocatalytic activity, together with a reduction of hydrogen peroxide production. In the work of Mazzapioda et al [3], a nonstoichiometric calcium titanate CaTiO 3-δ (CTO) was synthesized and used as an oxygen reduction reaction co-catalyst (together with Pt/C) in direct methanol fuel cells (DMFCs). The presence of the CTO additive promoted the oxygen reduction reaction (ORR) due to the presence of oxygen vacancies as available active sites for oxygen adsorption in the lattice.…”
Section: This Special Issuementioning
confidence: 99%